Bioassay study on effect of walnut leaf extracts on seed germination and seedling vigour of Cauliflower (Brassica oleracea var. botrytis) - Prasad, Birendra; Lavania, S.K.; Sah, V.K. (Indian Journal of Agroforestry, 2020)
Allelopathic effects of walnut leaf extracts on seed germination characteristics and seedling growth of cauliflower were investigated by a bioassay study as part of an effort to identify tolerant species to plant adjacent to walnut tree. Cauliflower seeds were subjected with walnut leaf extracts (20, 40, 60, 80, and 100 per cent) along with control for germination and seedling growth. Seed germination and its characteristics viz., speed of germination index, relative growth rate, germination index, germination energy as well as seedling length, weight and vigour index were affected by walnut leaf extracts in concentration dependent manner. MGT and T50 were indicated the higher values for increased leaf extract concentration while control found significantly lowest. Significant reduction in seed germination and seedling vigour were observed by the application of walnut leaf extracts as compared to control.